Análise crítica da Norma Brasileira ABNT NBR 16401-1 (Instalações de Ar Condicionado - Sistemas Centrais e Unitários parte 1 - Projeto das Instalações), 16401-2 (Parâmetros de Conforto Térmico) e 16401-3 (Qualidade do Ar Interior) - José Carlos Alfredo (2011)
The present issue turns around Air-conditioning installation and aims to study the Brazilian Standard ABNT NBR 16.401/2008 (Air-conditioning Installations Central and Unitarian Systems, parts 1, 2 and 3, respectively, Installations Projects, Thermal Comfort Parameters,and Indoor Air Quality). Its goal is to present and make it easier to understand, as well as to stimulate a reflection around the same Standard, directed to students, professors, professionalson that area and everyone interested into it. It will be also compared to other similar Norms, Resolutions and Regulations; it intends to recognize its impacts in differents sectors, including maintenance, and to suggest improvements for its new future edition. As this Norm has been elaborated taking advantage of previous acquired experience of international Regulations, most of it from American Society of Heating, Refrigerating and Air- Conditioning Engineers, and having in mind that such regulations are updated regularly from time to time, some aspects of the Brazilian Standard demand already to be updated. In firstplace, this dissertation presents the basic refrigeration cycle and its differents kinds of equipaments; secondly, it presents the Brazilian Standard ABNT NBR 16.401/2008 according to other Standards, Resolutions and Regulations; thirdly, it promotes the debate and criticalanalysis of the Norm for study and its practical utilization. To conclude the study, presents its final considerations as well as suggestions for new works. The methodology for present study we took lectures and made an analysis of Brazilian and International Regulations on the subject, we held meetings with the Brazilian Refrigeration, Air-conditioning, Ventilation and Heating Association; other meetings with ABNT (CB-55) and similar meetings with professionals on that area, not to mention, beside all theoretical-reflexive process, the professional experience of the authors nineteen years on the job. We know that knowledge is acquired through different ways, from the basic lessons held in elementary school and going on and on by means of continual research process, so that, when we got to have the knowhow, people start to use and test it on daily life, at work, at school or at both. Under this perspective, the development of this study is significant because through it we can seize a number of opportunities to improve, which can be showed by comparatives thoughts over the Brazilian Standard, other Standards, Regulations and Resolutions around the theme, and the authors own reflections. We believe that, if the opportunities to improve marked on this study are seized, that is, periodical updating, orthographic revision, air filter revision, a clearer definition of its goal, a better definition of what really means central air-conditioning system, the introduction of the term circuit, and much more, our country will enjoy of an excellentNorm on air-conditioning, thermal comfort and Indoor Air Quality. This, obviously, would attend better Brazilian market demands and expectations in terms of refrigeration and airconditioning